Airborne fiber size characterization in exposure estimation: Evaluation of a modified transmission electron microcopy protocol for asbestos and potential use for carbon nanotubes and nanofibers. Issue 5 (12th February 2015) - Dement, John M.; Kuempel, Eileen D.; Zumwalde, Ralph D.; Ristich, Anna M.; Fernback, Joseph E.; Smith, Randall J.
<x xml:space="preserve">Abstract</x> Background Airborne fiber size has been shown to be an important factor relative to adverse lung effects of asbestos and suggested in animal studies of carbon nanotubes and nanofibers (CNT/CNF). Materials and Methods The International Standards Organization (ISO) transmission electron microscopy (TEM) method for asbestos was modified to increase the statistical precision of fiber size determinations, improve efficiency, and reduce analysis costs. Comparisons of the fiber size distributions and exposure indices by laboratory and counting method were performed. Results No significant differences in size distributions by the ISO and modified ISO methods were observed. Small but statistically‐significant inter‐lab differences in the proportion of fibers in some size bins were found, but these differences had little impact on the summary exposure indices. The modified ISO method produced slightly more precise estimates of the long fiber fraction (>15 μm). Conclusions The modified ISO method may be useful for estimating size‐specific structure exposures, including CNT/CNF, for risk assessment research. Am. J. Ind. Med. 58:494–508, 2015. © 2015 Wiley Periodicals, Inc.